Post-pandemic Pedagogy: Practices as/with Parents for Performances - Yadav, Binod Kumar (KMC Journal, 2025)
Reflecting on this time makes us think more than usual pedagogy and andragogy since over all pass percentage of the students and the quality education especially in Madhesh Province, Nepal seem deteriorating in spite of the huge investment from dynamic facets. However, some specific students from school and campus levels were/are found having better performances in their previous year(s) following the pandemic disruption, and this enforced me to explore the impacting factors behind their better performances. This study is a survey research having quan-qual design conducted using a semi-structured interview with 10 parents of elementary level students performing better. The collected data were analyzed statistically and descriptively. It was found that the parents’ involvement in the students’ academic activities especially for managing them for their schools, arranging the requirements morning and evening for homework/self-study at home, placing them with nearby tutors and after all having more curiosity about whether they could do any more for better performances of their children’s quality education remained its core indicators. Thus, this is the time for education stakeholders to adopt the collaborative actions with the parents for better performance of the students in all levels.